THE ACCESSIBILITY OF THE HEALTH SERVICE: USERS' AND HEALTH CARE PROFESSIONALS' PERCEPTIONS - Leonardo Oliveira Leão e Silva; Carlos Alberto Dias; Marina Mendes Soares; Suely Maria Rodrigues (Universidade Federal do Paraná, 2011)
This qualitative study aimed to understand how factors which hinder access to the Family Health Strategy are seen by health service users and health care professionals. The data was collected through semi-structured interviews with 27 health care professionals and 16 health service users of four Family Health Strategy units, and was analysed using Bardin's thematic content analysis. The results showed that in the perception of health service users and professionals alike, the principal obstacles to accessing the service were the unit's location, the local geographical characteristics, transport, inadequate clarification of the area covered by the unit, the lack or unpreparedness of the health care professionals, and - finally - urban violence. It is noted that although the Family Health Strategy is meant to be organized based on a territorial perspective, in practice the mapping out of the health situation is done without a full comprehension of areas' multiple characteristics.